Valuing the strategic option to sell life insurance business: Theory and evidence - Klumpes, Paul J.M.; Shackleton, Mark B. (Journal of Banking & Finance, 2000)
We present a simple put option pricing procedure within an asset–liability valuation model that can be used to estimate the incentives facing stock-based life insurance firms to voluntarily sell their businesses under various operating and regulatory conditions. Estimates are derived for samples of 11 sold firms and 24 continuing Australian life insurance companies over a period of industry consolidation. The put option values interact with other actuarial and accounting components of the fair value of these life insurance firms and are used to assess the effectiveness of accounting and actuarial measures of capital, under static or dynamic based solvency testing models.